Influence of Salary, Promotion, and Recognition toward Work Motivation among Government Trade Agency Employees - Asaari, Muhammad Hasmi Abu Hassan; Desa, Nasina Mat (Canadian Center of Science and Education, 2019)
Reward and work motivation are very important for an organization, as this can be used to direct the staffs towards achieving the goals of the organization. Moreover, rewarding and motivating efficient employees will boost the employee's productivity. This situation has no exception to a trade agency that has an objective to promote an ethical domestic trade while protecting the interests of the consumers. Moreover, its responsibilities include monitoring domestic trade, advocating and protecting consumers' rights, protection of intellectual properties as well as registration and governance of businesses. In exercising the responsibilities, the trade agency makes and reviews related laws and policies, monitors the prices of essential items and carries out enforcement activities to maintain a healthy domestic trade environment. Furthermore, the trade agency is also responsible for coordinating the policies, licensing, regulations, and activities related to the safety of petroleum, petrochemical and gas industry. The purpose of this research is to investigate the reward, namely salary, promotion, and recognition toward work motivation factors among employees in the trade agency situated in the southern state. Self-Administered questionnaires were used to collect information from the respondents in understanding their reward on salary, promotion, and recognition; and relating them to their work motivation. The result concludes that there is a positive and significant relationship between rewards and motivation. In a nutshell, it can be concluded that as the reward increase, the motivation of employees will also be increased